1969
DOI: 10.1037/h0027524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blocking an instrumental avoidance response: Facilitated extinction but persistence of "fear."

Abstract: Facilitation of avoidance extinction through response prevention was investigated under two levels of acquisition (three and eight successive avoidance trials) and three levels of blocking (5-sec. detainment and 15-or 60sec. trials with total avoidance response prevention). Subjects consisted of 82 albino rats. An independent test of fear reduction involved allowing Ss subsequently to approach the shock chamber for food. Results indicate that complete prevention of the response during the first five extinction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
54
4
2

Year Published

1970
1970
1984
1984

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 12 publications
7
54
4
2
Order By: Relevance
“…Bersh, Department of Psychology, Temple University, Philadelphia, PA 19122. indirect, consisting of demonstrations that responseprevention treatments may hasten avoidance extinction without promoting a parallel reduction in other indices of warning-signal aversiveness (cf. Coulter et al, 1969;Mineka & Gino, 1979). Similarly, Marrazo, Riccio, and Riley (1974) reported equivalent facilitation of avoidance extinction for groups of rats exposed either to the warning signal alone or to warning-signal/shock pairings during response prevention.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Bersh, Department of Psychology, Temple University, Philadelphia, PA 19122. indirect, consisting of demonstrations that responseprevention treatments may hasten avoidance extinction without promoting a parallel reduction in other indices of warning-signal aversiveness (cf. Coulter et al, 1969;Mineka & Gino, 1979). Similarly, Marrazo, Riccio, and Riley (1974) reported equivalent facilitation of avoidance extinction for groups of rats exposed either to the warning signal alone or to warning-signal/shock pairings during response prevention.…”
mentioning
confidence: 95%
“…The prevention of avoidance behavior during unreinforced exposure to a preshock warning signal greatly facilitates subsequent avoidance extinction (e.g., Baum, 1970;Coulter, Riccio, & Page, 1969;Page, 1955), with the degree of facilitation proportional to the amount of warning signal exposure (Bersh & Keltz, 1971;Shipley, Mock, & Levis, 1971). However, the basis for the effectiveness of avoidance-response-prevention procedures is controversial (Baum, 1970;Mineka, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, they suggested that competing responses are acquired during the response-prevention phase even when the CS is reinforced by shock, and that such responses decrease the resistance to extinction of the avoidance response when it can again occur. Other investigators (Bersh & Keltz, 1971;Coulter, Riccio, & Page, 1969) have also implicated competing responses (e.g., freezing) in the response-prevention effect. However, Bersh and Keltz still reserved an important role for Pavlovian extinction.…”
mentioning
confidence: 99%
“…Several studies have suggested that subjects may exhibit fear even when avoidance responding has ceased following extinction or flooding (Coulter, Riccio, & Page, 1969;Kamin, Brimer, & Black, 1963;Mineka & Gino, 1979; see also Starr & Mineka, 1977). These fmdings suggest that levels of conditioned fear may be higher than might be expected on the basis of avoidance response data.…”
mentioning
confidence: 99%